Sustainable Development and Environmental Tourism. The Case of Lake Karla – Thessaly, Greece - TRAKALA, Georgia; MARTINIS, Aristotelis; KARRIS, Georgios; MINOTOU, Charicleia; TSIROUKIS, Achilleas (Journal of Environmental Management and Tourism, 2023)
Sustainable development is the common ground between the three components: environment, economy, and society, which are also known as sustainability pillars. In this work, an attempt was made to investigate whether Lake Karla - Mavrovouni, supporting agriculture, biodiversity and cultural activities and being part of the Natura 2000 protected area network , in combination with the diverse topics of environmental education, can contribute for the sustainable development of local societies, with the contribution of the collective bodies of local self-government. For the holistic management of the protected area of the "Karla" lake, the managers must consider on the one hand the protection of the natural and cultural heritage and on the other hand the sustainable development of the area through the promotion of the natural and cultural heritage and the promotion of environmental tourism. For this purpose, managers need to know socio-economic and demographic characteristics of visitors. Here, questionnaire responses were used to investigate the profile, environmental perception, knowledge, and behavior of visitors . In total, more than 300 questionnaires were sent, and finally 161 questionnaires were fully answered, which constitute the research sample. The analysis of the results showed that the natural and cultural environment contribute to the sustainable development of the wider area of Lake Karla-Mavrovouni, highlighting through them serious advantages and opportunities to exploit the area by the local bodies .